2012
DOI: 10.1180/minmag.2012.076.8.43
|View full text |Cite
|
Sign up to set email alerts
|

Gas flow in Callovo-Oxfordian claystone (COx): results from laboratory and field-scale measurements

Abstract: To understand the fate and impact of gas produced within a repository for radioactive waste, a series of laboratory and field scale experiments have been performed on the Callovo-Oxfordian claystone (COx), the proposed host rock for the French repository. Results show the movement of gas is through a localized network of pathways, whose properties vary temporarily and spatially within the claystone. Significant evidence exists from detailed laboratory studies for the movement of gas along highly unstable pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 6 publications
2
37
1
Order By: Relevance
“…For the BGS test the sample was orientated with the long axis parallel to the bedding direction, whereas the LAEGO study was performed perpendicular to bedding. Despite the difference in core orientation, gas injection testing reported by Harrington et al (2012) also gave a high gas entry pressure similar to that reported here for a sample of COx orientated perpendicular to bedding. Therefore bedding direction does not have a major role in determining gas entry pressures and does not influence the underlying physics governing gas flow.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…For the BGS test the sample was orientated with the long axis parallel to the bedding direction, whereas the LAEGO study was performed perpendicular to bedding. Despite the difference in core orientation, gas injection testing reported by Harrington et al (2012) also gave a high gas entry pressure similar to that reported here for a sample of COx orientated perpendicular to bedding. Therefore bedding direction does not have a major role in determining gas entry pressures and does not influence the underlying physics governing gas flow.…”
Section: Discussionmentioning
confidence: 48%
“…Figure 7 shows the interpretation of the onset of gas migration in COx. A three-stage interpretation has been postulated, which fits all the observations of the BGS and LAEGO, and also previously published results (Horseman et al 1996(Horseman et al , 2004Angeli et al 2009;Harrington et al 2009Harrington et al , 2012.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In general, at the laboratory scale, the initial conditions are a fully water-saturated medium subjected to a gas pressure of given amplitude, until gas passage is detected by varying means. However, no consensus exists as the exact phenomena involved in the gas migration (or breakthrough) through water-saturated clayrocks [3,20,22,[24][25][26][27][28][29]. Rather, several mechanisms are considered.…”
Section: Gas Migration Mechanismsmentioning
confidence: 99%
“…Cylindrical test specimens with an external diameter of 60 mm were manufactured by a combination of hand-trimming using a tubular former with a sharpened leading edge (Horseman & Harrington 1994) and machine lathing (Harrington et al 2012). Sample lengths were 53.9, 60.0 and 59.7 mm, respectively, for samples CRT-1, CRT-2 and CRT-3.…”
Section: Figmentioning
confidence: 99%